2017
DOI: 10.22159/ajpcr.2017.v10i11.20640
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Sepsis Through Sepsis Markers and Sepsis Index Through Flow Cytometry Technology

Abstract: Objective: Sepsis is a major medical challenge, and remains a burden by showing minimal symptoms, non-specific manifestation which leads to the high-mortality rate. The major cause of high mortality rate is due to the diagnostic pitfalls. The sepsis mechanism involves immune suppression associated with multiorgan dysfunction, uncontrolled infection, and death. This study aims to use new parameters in diagnosis of sepsis particularly neutrophil CD64 (nCD64), monocyte human leukocyte antigen-DR (mHLA-DR), perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Also, the study by Streimish et al [22] demonstrated that the sensitivity of CD64 was 78% and the specificity was 59%. The diagnostic efficacy of sensitivity and specificity nCD64 varied from 26 to 97% and 71 to 100%, respectively [24]. Thus, previous reports considered nCD64 a specific but weakly sensitive test for bacterial infection, and therefore, it is better to use it in combination with another more sensitive biological marker [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study by Streimish et al [22] demonstrated that the sensitivity of CD64 was 78% and the specificity was 59%. The diagnostic efficacy of sensitivity and specificity nCD64 varied from 26 to 97% and 71 to 100%, respectively [24]. Thus, previous reports considered nCD64 a specific but weakly sensitive test for bacterial infection, and therefore, it is better to use it in combination with another more sensitive biological marker [25].…”
Section: Discussionmentioning
confidence: 99%
“…The mean SI in controls is 74% while in probable sepsis 105% and in proven sepsis is 180%. The pilot study by Chauhan et al [24] on adults in ICU units indicated that the diagnosis of sepsis is better through the combination of nCD64, mHLA-DR, and sepsis index for better diagnosis of these patients in comparison with all other available modalities. Similarly, the study by Pradhan et al [6] revealed that sepsis index was significantly higher in infected than noninfected neonates and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that flow analysis is superior to all other currently available modalities for detecting sepsis in adults. 24 …”
Section: Discussionmentioning
confidence: 99%
“…2,3 Early diagnosis of sepsis is important for making crucial decisions regarding the therapeutic administration of antimicrobials in a strategic and time-bound manner. 4 The most reliable diagnostic tool for neonatal sepsis is the blood culture test, which is considered the gold standard. 5 Commonly used nonculture-based diagnostic tests include total and differential white blood cell (WBC) counts, absolute and immature neutrophil counts, and the ratio of immature to total neutrophils.…”
Section: Introductionmentioning
confidence: 99%